Innovative Strategies in Employee Turnover Management: A Systematic Review of Best Practices and Their Impact on Employee Retention in the Hospitality Industry - Laksmi, Ida Ayu Nyoman Widia; Tobing, Diana Sulianti K.; Setyanti, Sri Wahyu Lelly Hana; Handriyono, Handriyono (International Review of Management and Marketing, 2026)
The hotel sector has significant problems due to elevated personnel turnover, adversely affecting operational efficiency and client satisfaction. This project aims to explore novel techniques for reducing staff turnover and improving retention in the hospitality industry. The research does a systematic literature review (SLR) to assess effective approaches that reduce turnover and enhance employee engagement. The findings highlight the essential importance of excellent Human Resource Management (HRM) practices, which include thorough recruitment, ongoing training, and employee empowerment through inclusive decision-making. These measures have been recognized as essential factors in reducing turnover by fostering a positive work environment and enhancing job satisfaction. Moreover, transformational leadership, which advocates for employee empowerment and well-being, dramatically enhances retention. (1) The research underscores the significance of technology, particularly Decision Intelligence (DI), in streamlining operations and elevating work quality, thereby promoting staff retention. Moreover, Corporate Social Responsibility (CSR) efforts that emphasize employee welfare and environmental sustainability are crucial in strengthening employee loyalty and commitment. (2) This article provides essential insights for hotel managers and HR professionals aiming to use new techniques to reduce turnover, promote retention, and improve organizational performance in a competitive market.